Degradation capacities of bacteria and yeasts isolated from the gut of Dendroctonus rhizophagus (Curculionidae: Scolytinae) - Briones-Roblero, Carlos I; Rodríguez-Díaz, Roberto; Santiago-Cruz, José A; Zúñiga, Gerardo; Rivera-Orduña, Flor N (Folia microbiologica, 2017)
Bark beetles (Curculionidae: Scolytinae) feed on the xylem and phloem of their host, which are composed of structural carbohydrates and organic compounds that are not easily degraded by the insects. Some of these compounds might be hydrolyzed by digestive enzymes produced by microbes present in the gut of these insects. In this study, we evaluated the enzymatic capacity of bacteria (Acinetobacter lwoffii, Arthrobacter sp., Pseudomonas putida, Pseudomonas azotoformans, and Rahnella sp.) and yeasts (Candida piceae, Candida oregonensis, Cyberlindnera americana, Zygoascus sp., and Rhodotorula mucilaginosa) isolated from the Dendroctonus rhizophagus gut to hydrolyze cellulose, xylan, pectin, starch, lipids, and esters. All isolates, with the exception of C. piceae, showed lipolytic activity. Furthermore, P. putida, P. azotoformans, C. americana, C. piceae, and R. mucilaginosa presented amylolytic activity. Esterase activity was shown by A. lwoffii, P. azotoformans, and Rahnella sp. Cellulolytic and xylanolytic activities were present only in Arthrobacter sp. and P. azotoformans. The pectinolytic activity was not recorded in any isolate. This is the first study to provide evidence on the capacity of microbes associated with the D. rhizophagus gut to hydrolyze specific substrates, which might cover part of the nutritional requirements for the development, fitness, and survival of these insects.
Keywords: gastrointestinální trakt; biotransformace; Biotransformation; Yeasts; organické látky; kvasinky; Animals; Bacteria; nosatcovití; zvířata; Gastrointestinal Tract; Organic Chemicals; Weevils